The short- and long-term career effects of graduating in a recession: hysteresis and heterogeneity in the market for college graduates - Philip Oreopoulos; Till von Wachter; Andrew Heisz (Institute for the Study of Labor (IZA), 2008)
This paper analyzes the long-term effects of graduating in a recession on earnings, job mobility, and employer characteristics for a large sample of Canadian college graduates using matched university-employer-employee data from 1982 to 1999. The results are used to assess the role of job mobility and firm quality in the propagation of shocks for different groups in the labor market. We find that young graduates entering the labor market in a recession suffer significant initial earnings losses that, on average, eventually fade after 8 to 10 years. Labor market conditions at graduation affect firm quality and job mobility, which can account for 40-50% of losses and catch-up in our sample. We also document that higher skilled graduates suffer less from entry in a recession because they switch to better firms quickly. Lower skilled graduates are permanently affected by being down ranked to low-wage firms. These adjustment patterns are consistent with differential choices of intensity of search for better employers arising from comparative advantage and time-increasing search costs. All results are robust to an extensive sensitivity analysis including controls for correlated business cycle shocks after labor market entry, endogenous timing of graduation, permanent cohort differences, and selective labor force participation.
urn:nbn:de:101:1-2008071130
Keywords: J62; 330; Job search; hysteresis; college graduates; cost of recessions; Gehalt; Erwerbsverlauf; Hochschule; Qualifikation; Arbeitsmarkt; Wirtschaftslage; Kanada